Backward sled pulling load-velocity relationship in youth: a backward-forward comparison - Uthoff, A.; Cronin, J. (Journal of Science in Sport and Exercise, 2020)
Purpose: To establish the load-velocity relationships during backward sled pulling and compare this to forward sled pulling and determine the reliability of running speeds and associated load-velocity regression slopes in youth athletes. Methods: Twenty-one boys (age, 13.6 ± 0.28 years old; height, 1.72 ± 0.09 m; mass, 66.1 ± 8.2 kg; maturity, 0.57 ± 0.72 years from peak height velocity) performed backward and forward resisted running on three occasions. Load-velocity relationships were established using an un-resisted sprint and resisted sled pull with loads of 25%-81% body mass (BM) in both directions, and the reliability of sprint times at each load and the load-velocity regression slopes were examined. Results: The load-velocity data was reliable across multiple testing occasions for backward (CV = 7.2%; ICC 0.67-0.91) and forward sled pulling (CV = 7.2%; ICC 0.66-0.91). From the regression lines (R2 = 0.99; P = 0.01), it was observed that averaged loads across the sample of 31%, 46% and 61% BM resulted in 27%, 38% and 48% decrease in velocity during backward sled pulling and 23%, 33% and 43% during forward sled pulling. Increasing backward and forward loads by ~ 13% and ~ 15% BM respectively, reliably resulted in ~ 10% decreases in velocity. Conclusion: If contractile overload of the lower limbs is a focus of training then practitioners should preferentially use backward sled pulling. Both backward and forward sled pulling can be used in a similar manner regarding loading, though backward velocity is more sensitive to load and therefore overloading backward motion should be prescribed with this in mind.